Doença de Parkinson x Qualidade de vida: perspectiva dos cuidadores - Silva, Andrieli Cordeiro da (2018)
Purpose: To identify the speech therapy models used in treating dysarthria in patients with Parkinson’s Disease. Research Strategy: A search took place where studies published since 2008 were selected, using the key words “speech therapy” and “Parkinson’s disease”, “speaks” and “Parkinson’s disease” or “Parkinson”, and “dysarthria” and Parkinson’s disease” or “Parkinson”. Selection Criteria: The studies were selected by two examiners independently, taking some inclusion criteria into consideration: publications between 2008 and 2018, research involving human beings only, the use of speech therapy methods employed in the rehabilitation of dysarthria in Parkinson’s disease patients. Data Analysis: Studies related to speech therapy models for speech and voice disorders associated to Parkinson’s disease were selected, and the studies that made use of technologies for speech rehabilitation for Parkinson’s disease patients. Results: The search strategy resulted in 857 articles, of which only 15 reached the established selection criteria. Conclusion: There are many therapy models specifically to Parkinson’s disease; however, it is realized that the more structured models comprehend the vocal therapy and new technologies are being proposed, for example, online intervention and long distance.